Measurement in public sector financial reporting : theoretical basis and empirical evidence - Caruana, Josette; Bisogno, Marco; Sicilia, Mariafrancesca (Emerald studies in public service accounting and accountability, 2023)
Financial measurement can be difficult, especially in the public sector where accurate and reliable reporting is imperative for public trust, legality, accountability, and long-term sustainability of activities. Measurement in Public Sector Financial Reporting brings together theoretical arguments and empirical evidence to fuel the debate on measurement approaches in public sector financial reporting. Understanding that various dimensions of value need to be explored in order to reveal methods for providing a more comprehensive public sector view, Measurement in Public Sector Financial Reporting presents a constructive and thoughtful analysis of possible valuation methodologies for the public sector context and related peculiarities and critical issues. The chapters consider both theory and practice, providing a holistic showcase for both practitioner and academic viewpoints. The authors develop discussions and consolidate knowledge, providing a substantial contribution to an international debate. This second volume of Emerald Studies in Public Service Accounting and Accountability recognises the unique characteristics of public sector assets, liabilities, and the other elements of financial statements. The views presented in the chapters make the contents useful for those who are involved, interested in, or responsible for the preparation of public sector financial reporting and related standards.